2020
DOI: 10.21203/rs.3.rs-21074/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen rich water (HRW) induces plant growth and physiological attributes in fragrant rice varieties under salt stress

Abstract: Hydrogen is an important molecule, exerting antioxidant ability in plants and animals through antioxidant enzymes, which can be dissolved in water. Previous studies have showed that application of hydrogen rich water (HRW), containing a high concentration of hydrogen, plays an important role in enhancing drought tolerance and alleviating the metal stress in plants. However, the effects of HRW on plant growth and physiological attributes in fragrant rice varieties under salt stress are still unclear. A pot expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have noted a comparable morphological advancement in barley where subjecting HRW to drought circumstances resulted in an increase in the rate of seed germination and a reduction in the rate of inhibition of seedling growth 31 . Furthermore, the treatment of rice plants with HRW resulted in an increase in both plant height and dry weight 32 . Wheat seedlings, altering their physical traits to manage drought stress, frequently employ diverse strategies to confront limited water availability [33][34][35] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have noted a comparable morphological advancement in barley where subjecting HRW to drought circumstances resulted in an increase in the rate of seed germination and a reduction in the rate of inhibition of seedling growth 31 . Furthermore, the treatment of rice plants with HRW resulted in an increase in both plant height and dry weight 32 . Wheat seedlings, altering their physical traits to manage drought stress, frequently employ diverse strategies to confront limited water availability [33][34][35] .…”
Section: Discussionmentioning
confidence: 98%
“…These enzymes, such as superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT), are crucial in mitigating oxidative damage and reducing ROS production in plants. Among them, CAT is particularly noteworthy in www.nature.com/scientificreports/ scavenging H 2 O 2 to impede ROS formation 32,37,43 . Our study revealed that the application of HRW to plants led to enhanced levels of CAT, SOD, and APX activities relative to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that in humans H 2 can be administered to the lungs [12], as a drink [13], or can even be used as a topical treatment [14]. For plants, HRW can be supplied to the soil [15], the feed water [16] or foliage [17], and the atmosphere can be augmented with H 2 gas [18]. Alternatively, H 2 can be supplied to biological tissues via a donor molecule, which will release H 2 in the needed location.…”
Section: Introductionmentioning
confidence: 99%